Heterogeneity of reasons for attendance in frequent attenders of emergency departments and its relationship to future attendance. Issue 1 (29th June 2021) - Hotham, Richard; O'Keeffe, Colin; Stone, Tony; Mason, Suzanne M; Burton, Christopher
Abstract : Background: EDs globally are under increasing pressure through rising demand. Frequent attenders are known to have complex health needs and use a disproportionate amount of resources. We hypothesised that heterogeneity of patients' reason for attendance would be associated with multimorbidity and increasing age, and predict future attendance. Method: We analysed an anonymised dataset of all ED visits over the course of 2014 in Yorkshire, UK. We identified 15 986 patients who had five or more ED encounters at any ED in the calendar year. Presenting complaint was categorised into one of 14 categories based on the Emergency Care Data Set (ECDS). We calculated measures of heterogeneity (count of ECDs categories and entropy of categories) and examined their relationship to total number of ED visits and to patient characteristics. We examined the predictive value of these and other features on future attendance. Results: Most frequent attenders had more than one presenting complaint type. Heterogeneity increased with number of attendances, but heterogeneity adjusted for number of attendances did not vary substantially with age or sex. Heterogeneity was associated with the presence of one or more contacts for a mental health problem. For a given number of attendances, prior mental health contact but not heterogeneity was associated with further attendance. Conclusions: Heterogeneity of presenting complaint can be quantified and analysed for ED use: it is increased where there is a history of mental disorder but not with age. This suggests it reflects more than the number of medical conditions.